2019
DOI: 10.1029/2019gc008469
|View full text |Cite
|
Sign up to set email alerts
|

Detrital Zircon Geochronologic Constraints on Patterns and Drivers of Continental‐Scale Sediment Dispersal in the Late Mississippian

Abstract: The Late Mississippian was a critical time interval in Laurentia's history, marking the transition from carbonate deposition on a stable platform, during the Early to Middle Mississippian, to extensive clastic deposition in the Pennsylvanian to Permian associated with the Laurentia‐Gondwana collision. In the U.S. midcontinent, Chesterian incised valley fill (IVF) systems that developed within a carbonate‐dominated platform provide new insights on the patterns and drivers of continental‐scale sediment dispersal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 77 publications
(195 reference statements)
0
2
0
Order By: Relevance
“…Paleogeographic maps and sediment dispersal in the Greater Permian Basin during (a) early Wolfcampian (synorogenic stage) and (b) late Leonardian (post‐orogenic stage). The schematic sediment dispersal map is based on previous studies (Gao, Perez, et al, 2020; Gehrels et al, 2011; Lawton et al, 2021; Liu et al, 2021; Soreghan & Soreghan, 2013; Soto‐Kerans et al, 2020; Thomas et al, 2020; Waite et al, 2020; Wang & Bidgoli, 2019; Wang et al, 2022; Xie et al, 2019) and core–rim ages reported in this study. Permission for using copyrighted early Wolfcampian and late Leonardian time slices of the Greater Permian Basin created by Colorado Plateau Geosystems Inc. is gratefully acknowledged.…”
Section: Discussionmentioning
confidence: 99%
“…Paleogeographic maps and sediment dispersal in the Greater Permian Basin during (a) early Wolfcampian (synorogenic stage) and (b) late Leonardian (post‐orogenic stage). The schematic sediment dispersal map is based on previous studies (Gao, Perez, et al, 2020; Gehrels et al, 2011; Lawton et al, 2021; Liu et al, 2021; Soreghan & Soreghan, 2013; Soto‐Kerans et al, 2020; Thomas et al, 2020; Waite et al, 2020; Wang & Bidgoli, 2019; Wang et al, 2022; Xie et al, 2019) and core–rim ages reported in this study. Permission for using copyrighted early Wolfcampian and late Leonardian time slices of the Greater Permian Basin created by Colorado Plateau Geosystems Inc. is gratefully acknowledged.…”
Section: Discussionmentioning
confidence: 99%
“…Grains of these ages are both abundant in upper Paleozoic in the Appalachian foreland on Laurentia, representing the Acadia and Taconic orogenies (e.g., Thomas et al, 2017), and in Mexico that was on Gondwana during the late Paleozoic, such as the Mississippian Lower Santa Rosa Formation in southeastern Mexico (Weber et al, 2009) and magmatism of 410-370 Ma in the Acatlan Complex, southern Mexico (Yañez et al, 1991). Although Paleozoic grains have been suggested to be transported from the Appalachians into the Arkoma shelf by a large transcontinental river (e.g., Wang and Bidgoli, 2019), the age distribution of the upper Mud Creek tuff is very different from that of the Stanley sandstone that is representative to the zircon age signature of the deep-water depositional environment in Laurentia margin. Therefore, Paleozoic grains in the upper Mud Creek tuff were most likely recycled from the approaching peri-Gondwana terranes and/or inherited from the inferred Gondwana arc.…”
Section: Discussion Of Old Grainsmentioning
confidence: 99%